Коминтерн, КИМ и молодежное движение (1919–1943): Сб. документов: В 2 т. – М.: Политиздат, 1977. – Т.1. 1919–1933. – 463 с.; Т.2.1934–1943. – 320 с. - ЗАБАРКО , Б.М. (Український історичний журнал, 1979)
.